Keandalan Sistem Lintasan Produksi Pembuatan Pipa - Taufik Taufik; Wirli Hidayanti (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2016)
Production process of power pole involves connected production process flow between machines. Thus, the company must ensure the machine availability during production runs. PT Kunango Jantan as a company that produces pole power also considers machine availability. The level of machine availability can be seen from the high level of machine reliability. However, the company is still not been able to guarantee the availability of the machine so it is necessary to study the reliability of the system to help to take the right policy in handling pipe production machinery maintenance. The first step is to determine the distribution of machine damage. Minitab 16 software was used determine the type of distribution and distribution parameters of each machine damage. In addition, mean time between failure (MTBF) was calculated to the pipe manufacturing machine. The machine reliability was obtained based on a formula and parameters. The determination of the system reliability was derived from the block diagram in accordance with the condition of machines in the field. The analysis was performed using fishbone diagram to propose an attempt to increase the machine reliability. The results of this study indicate that the machine reliability in good level since the reliability value is between 0.901 to 1.000. The machine reliability in a series circuit is smaller than the machine reliability in a parallel circuit. Rs and R values of the system were 0.980 and 0.998. R system shows that the system has a good performance with a chance of machine damage during production <0.002 (0.2%).